Environmental management strategy to control environmental and sanitary risks of hazardous waste in a category II-1 hospital in the province of Bagua - Cruz-Hoyos, Segundo Alipio (2024)
This study focuses on developing an environmental management strategy to mitigate the environmental and health risks of hazardous waste at Support Hospital II-1 in the province of Bagua. The objectives include performing an initial diagnosis of the management of this waste, assessing the associated risks, and characterizing the key factors to propose an effective strategy. The methodology included the characterization of hazardous waste generated during a week, using descriptive statistics to analyze daily volume and weight data. Hospital staff participated through questionnaires and checklists according to NTS No. 144-2018-DISA-DIGESA regulations. The results showed significant deficiencies in solid waste management, exposing staff and the environment to considerable risks. Among the most relevant findings, insufficient staff training and deficiencies in the infrastructure for the storage and transportation of hazardous waste were identified. Based on these results, an environmental management strategy was designed focused on improving the control of biocontaminated and chemical waste, using safety protocols and mitigation measures. This work concludes that the implementation of an effective environmental strategy is crucial to reduce the negative impacts on health and the environment, thus protecting hospital staff and the community.